The computational study on the aerodynamic characteristics of airfoils using fluent / Zulkifli Yahaya - Yahaya, Zulkifli (2005)
Steady-state, two-dimensional CFD calculations were made for the symmetry airfoil, NACA 0012 and cambered airfoil, WORTMANN FX 63-137 using the standard turbulence model, K-B model of commercial code, FLUENT. Comparisons of aerodynamics characteristics, pressure contours, and velocity vectors were made between the two airfoils. The effects of Reynolds numbers, angles of attack, and airfoil profiles on the airfoils were investigated. Results showed that for each and increased Reynolds number with corresponding angle of attack, the cambered airfoil has increasing and higher values of CL and Co than the symmetry airfoil. As the Reynolds number and the angle of attack are increased, the stagnation points of both airfoils are moved further backward to the lower surface. The cambered airfoil, WORTMANN FX 63-137, has clear pressure difference between the upper and the lower surfaces. The lower surfaces have higher pressure than upper surface. The highest pressure is at the leading edge, followed by the pressure at trailing edge. For symmetry airfoil, NACA 0012, 'ihe upper surface has the lowest pressure. As the Reynolds number and angle of attack are increased, the pressure difference between the upper and lower surfaces is increased. The highest pressure is at the leading edge. Upper surface of NACA 0012 airfoil has the highest velocity vectors. The leading edge has the lowest velocity vectors. For WORTMANN FX 63-137, the slowest velocity is at the leading and trailing edges. The lower surface has lower velocity vectors than the upper surface.